PATOLOGI DIGITAL GAME ONLINE MELALUI PENDIDIKAN ISLAM - Yunus Salik (STIT Islamic Village Tangerang, 2022)
The purpose of the study was to determine the impact of online game digital pathology and how to overcome it through Islamic religious education. This research uses qualitative research with pedagogical and normative approaches. The digital pathology that developed at UPT SD Negeri 177 Tokke, Malangke District, is an online game pathology that is around 4 hours a day used by students. Students who are excessive in playing games tend to have emotional feelings that are difficult to control, children admit to being quick to anger, sad, and annoyed when their parents suddenly stop their online game playing activities. The negative impact of online games causes students to be more active in thinking about how to advance to the next stage or how to beat their playing opponents without caring about the lessons at school. It is hoped that parents will pay more attention to their children when children spend their learning time playing online games that are less useful for academic achievement. In the prevention function, understanding function and alleviation function, only PAI teachers and school personnel handle these students. If the PAI teacher has experienced difficulties, especially now that the learning epidemic is still online, in handling these students, a supervisory function is applied, namely the school is assisted by the students' families in handling and supervising students addicted to online games.